THE EFFECTIVENESS OF PICTURE STORY BOOK APPLICATION TO WARDS UNDERSTANDING CULTURAL DIVERSITY IN ELEMENTARY SCHOOL LEVEL - Prasetia, Hendra (PD PGMI se Indonesia, 2023)
This study is aimed designed to test effectiveness of picture story book towards understanding Cultural diversity. The Research is proceeded as Experimented Research System with pre-test post-test control group design. The Subjects of this research are students grade IV Elementary School. The Data Collection of the research is used with tests. The Research Instrument is questionnaire with test questions about Cultural diversity. Hypothetical Measurement is applied in Wilcoxon. The Result of this Research states that the application of picture story book towards understanding Cultural Diversity is reached effective. The result is shown by Differentiations Grades by the class used Picture Books and not. The Distinctions received from Significance Test with 0,031 determined lower than 0,05 can be concluded that there are differences in the results of the pre-test and post-test in this experimental class group. Based on the results of the study in the control class, it was obtained that the significance value of 0.055 was greater than 0.05, so it any difference between the pre and post test results. It can be concluded that the use of picture story books is effective in understanding the cultural diversity of fourth grade elementary school students.